Vulpia ciliata Link - a Grass New to India - Naithani, H. B.; Bahadur, K. N. (Indian Forester, 1979)
Vulpia ciliuta Link, a grass of Mediterranean Europe, Western & Central Asia and North Africa, is recorded for the first time from India. It was collected at Nal Dehra, Disrict Simla (Himachal Pradesh) by a student of the Punjab University, Chandigarh. Notes on its nomenclature, description, habitat, distribution, etc., along with an illustration are provided to facilitate determination of this alien grass The Specimen is deposited in Herbarium DD.